Occult urinary incontinence in patients with anterior vaginal prolapse - Jędrzejczyk, Sławomir; Rutkowska, Beata; Wieczorek, Marek; Stetkiewicz, Tomasz; Lau, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2012)
Background: Pelvic Organ Prolapse (POP) often leads to lower urinary tract dysfunction. Most often patients suffer from stress, urge or mixed urinary incontinence. Symptoms of urinary incontinence frequently appear after POP surgeries. Incidence of stress urinary incontinence after severe grade of POP surgeries in women containing urine before surgery is present in 11-22% of cases. Aim of the study: To assess incidence of occult urinary incontinence diagnosed preoperatively, in women with anterior vaginal wall prolapse; assess incidence of stress urinary incontinence after anterior vaginal wall prolapse surgeries in patients with occult urinary incontinence diagnosed preoperatively, to perform a comparative assessment of selected urodynamic parameters evaluated before and after the anterior vaginal wall surgery. Material and methods : In our research we included 33 female patients, aged 41-76, operated in our Department between March 2008 and October 2009, who underwent pre- and postoperative urogynecological and urodynamic examinations. Results: In a preoperative examination occult urinary incontinence was diagnosed in 11 (33.36%) women. In the postoperative course, symptoms of stress urinary incontinence (SUI) were found in 6 (54.54%) from those 11 patients. Five patients were free of symptoms of LUTD. The difference between average bladder compliance (C) and maximum flow (Q max ) in pre- and postoperative urodynamic study was statistically significant. Conclusions : Occult urinary incontinence often occurs in patients with anterior vaginal wall prolapse. A cystocele correcting procedure is correlated with a high rate of postoperative stress urinary incontinence. Anterior vaginal wall prolapse surgery improves bladder compliance.